On τ-closed n-multiply ω-composition formations with Boolean sublattices - Zhiznevsky, P. (Algebra and Discrete Mathematics, 2010)
In the universe of finite groups the description of τ-closed n-multiply ω-composition formations with Boolean sublattices of τ-closed n-multiply ω-composition subformations is obtained.